1994
DOI: 10.1111/j.1748-720x.1994.tb01295.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Prescription Drug Misuse and Abuse: Defining the Problem and Seeking Solutions

Abstract: Each year, millions of individuals in the United States are treated for a variety of serious medical conditions with prescription drugs whose therapeutic benefits are well known. The vast majority of these medications are used to treat medical and psychiatric illnesses. Generally, they are used as prescribed, and contribute to a better quality of life for persons suffering from debilitating or life-threatening disorders.The fact that a small portion of these medications is diverted by those who seek their psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…17 In fact, only a relatively small percentage of prescription drugs are actually diverted to illicit use by doctors or patients. 18 Notably, of the four types of offenders involved in pharmaceutical diversion, deceptive patients are far and above the most likely source of diverted pharmaceuticals; 19 dated doctors (those who are out of touch or lax in their prescribing behavior) are a distant second, followed by impaired doctors. 20 Dishonest doctors are the least likely source of diversion, accounting for less than 2 percent of all pharmaceutical diversion.…”
Section: Pharmaceutical Diversionmentioning
confidence: 99%
“…17 In fact, only a relatively small percentage of prescription drugs are actually diverted to illicit use by doctors or patients. 18 Notably, of the four types of offenders involved in pharmaceutical diversion, deceptive patients are far and above the most likely source of diverted pharmaceuticals; 19 dated doctors (those who are out of touch or lax in their prescribing behavior) are a distant second, followed by impaired doctors. 20 Dishonest doctors are the least likely source of diversion, accounting for less than 2 percent of all pharmaceutical diversion.…”
Section: Pharmaceutical Diversionmentioning
confidence: 99%
“…Numerous national surveys, prescription drug abuse surveillance programs and other federally supported monitoring systems have shown a substantial rise in the abuse/misuse of prescription opioids over the past 15 years (Bergman & Dahl-Puustinen, 1989; Blumenschein, 1997; Borsack, 1986–1987; Cooper, Czechowicz, Petersen, & Molinari, 1992; Inciardi, Surratt, Stivers, & Cicero, 2009; Manchikanti, Fellows, Ailinani, & Pampati, 2010; McCabe, Teter, & Boyd, 2004; Monheit, 2010; Ruetsch, 2010; Simoni-Wastila & Tompkins, 2001; Strassels, 2009; Wilford, Finch, Czechowicz, & Warren, 1994; Zacny et al, 2003). The accessibility of these drugs to non-patients is the result of their unlawful channeling from legal sources to the illicit marketplace, which is commonly referred to as “drug diversion”.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data showed that greater numbers of people, especially young, college-aged adults, reported using a variety of pharmaceuticals for nonmedical purposes (Colliver, Kroutil, Dai, & Gfoerer, 2006; National Institute on Drug Abuse [NIDA], 2001). Although the category of nonmedical use includes several distinct patterns, including self-medication for physical and emotional conditions and functional use directed at increasing individual academic performance, it is the recreational aspects of this practice that have generated particular alarm in the public health literature as well as popular media (Harmon, 2005; McCarthy, 2007; Wilford, Finch, Czechowicz, & Warren, 1994). …”
Section: Introductionmentioning
confidence: 99%